The Influence Of The Role Playing Method On The Speaking Skills Of Students Mts Ainul Hasan Wonorejo Maron Probolinggo - Selvia Devi Agustin; Abd. Aziz; Zainuddin Zainuddin (Journal on Education, 2024)
The problem of educational methods is a problem that really needs attention, especially for educators, because choosing the right method will determine the success of a student in the learning process, on the other hand, if educators use inappropriate or ineffective method selection, it will cause poor learning monotonous and less successful. To provide a pleasant learning atmosphere for students, a teacher must know the ways or methods that must be applied, so that students are motivated to take part in learning activities. Therefore, students need game-based teaching methods. In addition to fulfilling the need for games and entertainment, the need for knowledge will also be fulfilled through the delivery of material using game methods, one of which is the Role Playing method.